Pengaruh Perubahan Tarif, Kemudahan Membayar Pajak, Sanksi Pajak, Dan Sosialisasi Pp Nomor 46 Tahun 2013 Terhadap Tingkat Kepatuhan Wajib Pajak Pelaku UmkmStudi Empiris pada Wajib Pajak Pelaku UMKM yang Terdaftar di KPP Pratama Salatiga - Noza, Claressa Ayu Amanda; Aris, Ak, M.Si, Drs. M. Abdul (2016)
This study aimed to analyze the effect of changes in rates, the ease of paying taxes, tax penalties, and dissemination of government regulation number 46 of 2013 on the level of tax compliance SMEs (empirical study on SMEs taxpayers listed in KPP Pratama Salatiga). This study uses a quantitative method using primary and secondary data obtained from questionnaires. The population in this study is the taxpayer SMEs listed on STO Salatiga. The number of samples in this study were 85 taxpayers. The analytical tool used include test the quality of data collection, the classic assumption test, test the accuracy of the model (goodness of fit), the coefficient of determination R², and hypothesis testing (statistical t-test). The results showed that: (1) changes significantly influence adherence rates to pay taxes, (2) ease of paying taxes significantly influence compliance to pay taxes. (3) tax penalties significantly influence compliance to pay taxes. (4) dissemination PP number 46 of 2013 have a significant effect on adherence pay taxes.